DESAIN PENGEMBANGAN KURIKULUM BAHASA ARAB: PENDEKATAN OTAK KANAN - Muhammad Yusuf (Universitas Islam Negeri Mataram, 2019)
This paper aims to discuss the development of the Arabic languagecurriculum based on the right brain approach. This paper relies on bibliographicsources in the form of books and articles (literature studies) which are in thescientific journal related to the subject matter. Reading the data of thought byacademics using a critical constructive approach and meaning of the substancewith content analysis. Based on the studies that have been conducted, the rightbrain approach in learning Arabic can be narrated as an axiomatic way ofthinking about how to learn Arabic by optimizing right brain functions whichinclude rhymes, rhythms, music, visual impressions, colors, and images. Thusthe purpose of learning Arabic is the students are able to obtain Arabic languageknowledge that is ready to be used in the field of scientific and practical social inthe community, in a way that is fun and full of enthusiasm. The method that canbe used is the psychological method. While in learning techniques in principle,it must be able to attract students’ interests and motivations, encourage studentsto think critically-creatively-holistically, and must encourage students to becooperative and interactive.